The preventive effect of Zingiber officinale essential oil on demyelination of corpus callosum in a cuprizone rat model of multiple sclerosis - Valiollah Moradi; Seyed Mostafa Ghanadian; Bahman Rashidi; Nazem Ghasemi; Gholamreza Dashti; Ebrahim Esfandiari (Mashhad University of Medical Sciences, 2023)
Objective: Multiple sclerosis (MS) is the most prevalent neurological disability among young adults. Anti-inflammatory drugs have shown to be effective in MS. The anti-inflammatory and antioxidative properties of Zingiber officinale (ginger) have been shown and proven in many phytotherapy studies. This study aimed to evaluate effects of ginger essential oil on preventing myelin degradation in a rat model of MS.Materials and Methods: In this study, we divided 49 rats into 7 groups; 4 control and 3 experimental groups that received 3 different dose of ginger essential oil (50, 100, and 150 mg/kg/day) for treatment of cuprizone-induced demyelinated rats. Basket test and transmission electron microscopy were performed in this study. Olig2 and Mbp genes and proteins were respectively evaluated by reverse transcription-polymerase chain reaction (RT-PCR) and enzyme-linked immunosorbent assay (ELISA).Results: Histologically, cuprizone created demyelination in the corpus callosum fibers. Remyelination of fibers was seen in the group treated with the medium dose of ginger essence, by toluidine blue staining. transmission electron microscopy (TEM) revealed increased thickness of the myelin of fibers in all 3 treated groups (p<0.05). Feeding by the medium dose of ginger essence significantly increased the levels of Mbp and Olig2 genes (p<0.05).  ELISA test showed that 100 mg/kg/day of ginger caused a significant difference between experimental and the cuprizone-induced groups (p<0.05).Conclusion: Our findings suggested that administration of ginger essential oil prevented demyelination and improved remyelination of rats` corpus callusom and can be used as an effective substance in the prevention of MS.